Multi-morphology lattices lead to improved plastic energy absorption. (September 2020) - Alberdi, Ryan; Dingreville, Rémi; Robbins, Joshua; Walsh, Timothy; White, Benjamin C.; Jared, Bradley; Boyce, Brad L.
Abstract: While lattice metamaterials can achieve exceptional energy absorption by tailoring periodically distributed heterogeneous unit cells, relatively little focus has been placed on engineering heterogeneity above the unit-cell level. In this work, the energy-absorption performance of lattice metamaterials with a heterogeneous spatial layout of different unit cell architectures was studied. Such multi-morphology lattices can harness the distinct mechanical properties of different unit cells while being composed out of a single base material. A rational design approach was developed to explore the design space of these lattices, inspiring a non-intuitive design which was evaluated alongside designs based on mixture rules. Fabrication was carried out using two different base materials: 316L stainless steel and Vero White photopolymer. Results show that multi-morphology lattices can be used to achieve higher specific energy absorption than homogeneous lattice metamaterials. Additionally, it is shown that a rational design approach can inspire multi-morphology lattices which exceed rule-of-mixtures expectations. Graphical abstract: Unlabelled Image Highlights: Multi-morphology lattices are composed using face-centered cubic (FCC) and body-centered cubic (BCC) unit cell architectures. Different multi-morphology lattice designs are inspired by mixture rules and a developed rational design framework. The topological arrangement of unit cell architectures plays a prominent role in determining energy-absorption performance. Primary collapse mode can be controlled through design so that it persists across different base materials. Improvements over both homogeneous lattice metamaterials and rule-of-mixtures expectations are driven by design.